Community perception on climate change and climate-related disaster preparedness in Kathmandu Valley, Nepal - Nehren, Udo; Subedi, Jishnu; Yanakieva, Ina; Sandholz, Simone; Pokharel, Jibraj; Chandra Lal, Ajay; Pradhan-Salike, Inu; Aris Marfai, Muh; Sri Hadmoko, Danang; Straub, Günther (JNRD - Journal of Natural Resources and Development, 2013)
Within the last decades, Kathmandu Valley in Nepal has been characterized by rapid population growth and related urbanization processes, leading to environmental degradation, pollution and supply bottlenecks in the metropolitan area. Effects of climate change are now putting additional stress on the urban system. In our research in Kathmandu, we carried out community and household surveys to analyze community perception on climate change and climate-related disaster preparedness. For this purpose, three categories of communities, 12 in all, were surveyed and interviewed: Squatter settlements, agricultural villages, and traditional villages. All settlements are located close to main rivers and therefore especially exposed to floods and droughts, and in slope position also to landslides. As a main result, we can conclude that people are generally aware of climate change and its potential consequences, such as climate change-related disasters. However, in their daily lives, climate change does not play a significant role and most communities have not taken any adaptation measures so far.
Keywords: Climate change; Kathmandu Valley; Disaster risk; Community perception; Preparednes